INDUSTRIALISASI DAN PROBLEMA INDONESIA (SUATU TINJAUAN "INDUSTRIALISASI SEMU" INDONESIA - Kausar Kausar (JIP ( Jurnal Industri dan Perkotaan ), 2010)
This writing aim to know the quasi industrialization in Indonesia. quasi industrialization in Indonesia different with other country. The concept of industrialization not clear and not focus, Indonesia want like west country, but Indonesia has different endowment factor. It's caused Indonesia doesn't have strong competition with the other country. Indonesia doesn't have entrepreneurship abilty and decision making process based on nepotism, colutive, make industrialization in Indonesia become quasi.